Análise do mercado de sementes de soja no Rio Grande do Sul - Cirino, Jean Carlos (2010)
The soy beans market is adjusting a restructuring since the liberation of Roundup Ready® (RR) technology by federal government in Brazil. In the latest years, the sector started to increase the internal sales, through the agriculturists consciousness about the seeds, more productive and with higher technology than pirate seeds. However, the seed market, many times is evaluated through empirical numbers that end up not representing the exact tendencies of the sector. This study has as a goal a detailed evaluation of numbers that move this market. For this it was used as a reference basis two documents sent by seed farmers to the MAPA: the relation of fields for seeds production (RC), and the production and seeds business (MP). Both documents are processed by APASSUL according to the term of technical cooperation among MAPA(SEFIA/RS), CSM and APASSUL. The observed notes are about the crops in 2005/2006, 2006/2007 and 2007/2008. The results presented a growth in legal seeds production and business, confirming the growth in the sector. It was also possible to note the new breeders that have been growing in this market. About the cultivars usage, that previously, was restrict to some materials, the scenario shows an increasing stratification with similar tendency verified in the market participation as a breeder. Note that for every hectare approved less than a half ton of seeds is commercialized, and low level of marketing is the highest risk factor.